Molecular genomic and epigenomic characteristics related to aspirin and clopidogrel resistance - Jei Kim; Byoung-Soo Shin; Dae-Hyun Kim; Dong-Ick Shin; Seong Hwan Ahn; Jae Guk Kim; Su Hyun Ryu; Hye Rin Moon; Hyun Goo Kang; Hyeseon Jeong; Kyu Sun Yum; Hee-Yun Chae; et al. (BMC, 2024)
Abstract Background Mediators, genomic and epigenomic characteristics involving in metabolism of arachidonic acid by cyclooxygenase (COX) and lipoxygenase (ALOX) and hepatic activation of clopidogrel have been individually suggested as factors associated with resistance against aspirin and clopidogrel. The present multi-center prospective cohort study evaluated whether the mediators, genomic and epigenomic characteristics participating in arachidonic acid metabolism and clopidogrel activation could be factors that improve the prediction of the aspirin and clopidogrel resistance in addition to cardiovascular risks. Methods We enrolled 988 patients with transient ischemic attack and ischemic stroke who were evaluated for a recurrence of ischemic stroke to confirm clinical resistance, and measured aspirin (ARU) and P2Y12 reaction units (PRU) using VerifyNow to assess laboratory resistance 12 weeks after aspirin and clopidogrel administration. We investigated whether mediators, genotypes, and promoter methylation of genes involved in COX and ALOX metabolisms and clopidogrel activation could synergistically improve the prediction of ischemic stroke recurrence and the ARU and PRU levels by integrating to the established cardiovascular risk factors. Results The logistic model to predict the recurrence used thromboxane A synthase 1 (TXAS1, rs41708) A/A genotype and ALOX12 promoter methylation as independent variables, and, improved sensitivity of recurrence prediction from 3.4% before to 13.8% after adding the mediators, genomic and epigenomic variables to the cardiovascular risks. The linear model we used to predict the ARU level included leukotriene B4, COX2 (rs20417) C/G and thromboxane A2 receptor (rs1131882) A/A genotypes with the addition of COX1 and ALOX15 promoter methylations as variables. The linear PRU prediction model included G/A and prostaglandin I receptor (rs4987262) G/A genotypes, COX2 and TXAS1 promoter methylation, as well as cytochrome P450 2C19*2 (rs4244285) A/A, G/A, and *3 (rs4986893) A/A genotypes as variables. The linear models for predicting ARU (r = 0.291, R2 = 0.033, p < 0.01) and PRU (r = 0.503, R2 = 0.210, p < 0.001) levels had improved prediction performance after adding the genomic and epigenomic variables to the cardiovascular risks. Conclusions This study demonstrates that different mediators, genomic and epigenomic characteristics of arachidonic acid metabolism and clopidogrel activation synergistically improved the prediction of the aspirin and clopidogrel resistance together with the cardiovascular risk factors. Trial registration URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03823274.